Sexual dimorphism in some psycho-neuro-endocrine parameters at human - Nataliya Kozyavkina; Igor Popovych; Dariya Popovych; Walery Zukow; Igor Bombushkar (Kazimierz Wielki University, 2021)
Background. Despite the well-documented relationships between HRV, EEG and anxiety parameters, studies of their sexual dimorphism, judging by the results of the meta-analysis, have so far been conducted separately. The purpose of this study is to clarify sexual dimorphism in almost synchronously registered psycho-neuro-endocrine parameters. Materials and Methods. The object of observation were practically healthy volunteers: 30 females (30÷76 yr) and 31 males (24÷69 yr). In basal conditions we recorded the ongoing HRV and EEG, determined serum levels of testosterone, calcitonin, cortisol, aldosterone, and triiodothyronine, estimated the severity of the trait and reactive anxiety. After 4 or 7 days, repeated testing was performed. Results. Regardless of age, females differ significantly from males, except for drastically lower levels of testosterone and calcitonin by definition (but not cortisol, aldosterone and triiodothyronine), lower levels of HRV-markers of sympathetic tone (but not heart rate), reactive anxiety, and beta-rhythm asymmetry. On the other hand, trait anxiety, levels of HRV-markers of vagal tone, variability and amplitude of the beta-rhythm, and its power spectral density (PSD) in 12 loci (maximum differences in T6, F3, and T3 loci), amplitude of the theta-rhythm and its PSD in 16 loci (maximum differences in F3, C3, and T3 loci), PSD of the alpha-rhythm in T3, T6, F7, and T4 loci as well as entropy of PSD in F7 and F8 loci are significantly higher in females than in males. The listed parameters are determined by testosterone for 31,7%, and calcitonin for 26,3%. The method of discriminant analysis revealed 20 EEG and 6 HRV parameters as well as trait and reactive anxiety, based on the totality of which males can be retrospectively recognized (without testosterone and calcitonin) with an accuracy of 90,3%, and females with an accuracy of 88,3%. Conclusion. The revealed differences between the sexes were not influenced by at least two bioactive factors, that is, they are robust sex markers.